Clinical Profile and Induction Outcome of Children with T-cell Acute Lymphoblastic Leukemia and T-cell Lymphoblastic Lymphoma - Arshed, Awais; Nasarullah, Faran; Shahid, Samra; Tahir, Muhammad; Farah, Tanzeela; Ghafoor, Tariq (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the clinical profile and induction outcome in children diagnosed with T-cell acute lymphoblastic leukaemia and lymphoblastic lymphoma.Study Design: Cross-sectional study.Place and Duration of Study: Paediatric Oncology Unit, Combined Military Hospital, Rawalpindi Pakistan, from Jan 2012 to Dec 2020.Methodology: One hundered and twenty-one diagnosed patients of T-ALL and LBL were evaluated with bone marrow biopsy and Contrast-enhanced CT scan of the active region after induction chemotherapy with Dexamethasone, Vincristine, Asparaginase and Daunorubicin along with intrathecal Methotrexate. This was carried out on days-8 and 29 to determine the early remission status and end of induction response, respectively.Results: Out of 121 patients, 99(81.8 %) had T–ALL, while 22(18.18%) had LBL. Day-8 assessment showed that 94(77.7%) patients were rapid early responders, 24(19.4%) were slow early responders, while 3(2.4%) patients expired before the day eight assessment. Day-29 bone marrow assessment of 88 T-ALL patients showed complete remission in 77 patients (87.5%), incomplete remission in 5(5.68%) patients and treatment failure in 2(2.27%) patients. 20(93.1%) patients with LBL achieved remission by Day-29, while 2 (0.02%) LBL patients died before the Day-29 assessment.Conclusion: The remission induction rates and mortality rates in our setup are encouraging and comparable to international data. Further improvements can be made by early management of the affected cases and more accessible pediatric oncology health services.